The Cryoballoon vs Irrigated Radiofrequency Catheter Ablation (CIRCA-DOSE) Study Results in Context. Issue 1 (2020) - Andrade, Jason G; Deyell, Marc W; Verma, Atul; Macle, Laurent; Khairy, Paul
No abstract available